DETERMINAN KESEDIAAN NELAYAN MENGAGUNKAN SERTIFIKAT HAK ATAS TANAH DAN DAMPAKNYA TERHADAP PENDAPATAN - Mahpud Mahpud; Satyawan Sunito; Idqan Fahmi (Jurnal Manajemen & Agribisnis, 2016)
This study aimed to analyze factors which influence or encourage the fishermen as the participants in land right certification program to be willing to secure their land certificate to obtain loans and to analyze the impact of land certification program for the fishermen to increase their income and welfare. The study was conducted in Indramayu as an area which has a fisherman land certification program. The data obtained in this study were analyzed by logistic regression and multiple linear regression. The logistic regression analysis was performed by using feasibility test model (goodness of fit) and Nagelkerke R Square Coefficient. Moreover, the multiple linear regression analysis was performed by using F Test and determination coefficient analysis (R²). The results showed that the fishermen status and educational background, land width, ownership of other assets and side business are included as factors that significantly influence the interest to use their land certificate obtained from "Fishermen Empowerment Program and Small-Scaled Fishery Businesses through the Certification of Land Right” as their collateral. The results were supported by highlighting that p-value for each variable is smaller than 0,10 and the educational factor has a significant effect which is higher than 0,009 compared to other factors. Having a higher education level encourages the fishermen to secure their land certificates in order to obtain capital in increasing their income and welfare.Keywords: logistic regression, fishermen, income, land certificate, welfare